Case Report: Strawberry Disease in Farmed Chilean Rainbow Trout. Issue 1 (2nd January 2016) - Sandoval, Carlos; Infante, Jorge; Abad, Jessica; Ferguson, Hugh W.; Paredes, Enrique; Valdebenito, Samuel; Yáñez, Alejandro J.; Ilardi, Pedro; Avendaño-Herrera, Ruben
Abstract: Strawberry disease is a chronic, nonlethal skin condition that affects Rainbow Trout Oncorhynchus mykiss in the United States and several European countries, where it is also known as red-mark syndrome. We provide the first identification and characterization of three strawberry disease outbreaks occurring at two aquaculture farms in southern Chile. Clinically affected fish weighing an average of 400 g presented multiple bright-red, usually raised, skin lesions on the flank, ventral surface, and dorsal surface. A PCR using Rickettsia -like-organism (RLO)-specific primers was performed on nine affected fish, and all skin samples were positive for the RLO 16S ribosomal RNA sequence. All PCR results for Flavobacterium psychrophilum and other bacterial and viral pathogens were negative. Histopathological examination of the skin lesions revealed extensive dermatitis, with severe lymphocytic infiltration in advanced cases. This report is the first to describe strawberry disease in farmed Chilean Rainbow Trout. Additional studies are needed to evaluate the risk for Rainbow Trout culture; fish challenge experiments should be performed to fulfill Koch's postulates and to demonstrate that RLO is the cause of this disease. Received December 27, 2014; accepted October 23, 2015.